Rekonstruksi Paradigma Keilmuan Modern: Sintesis Induktivisme Bacon, Logika Kausal Mill, dan Positivisme Comte - Indriani, Indriani; Wiyanto, Sandi; Widia, Widia; Nurhayati, Nurhayati; Ardiansyah, Andi; Zanki, Amir Basari (Universitas Muhammadiyah Magelang, 2026)
The development of modern scientific methodology reveals a growing tendency toward partial approaches that separate data exploration, causal analysis, and empirical verification, which may lead to epistemological reductionism in research practices. This study aims to reconstruct the scientific paradigm through a synthesis of Francis Bacon’s inductivism, John Stuart Mill’s causal logic, and Auguste Comte’s positivism as an integrative methodological framework. This research employs a library research method by examining primary works of Bacon, Mill, and Comte, as well as relevant journal articles published within the last five years. Data analysis is conducted using a comparative approach to assess the functions, strengths, and limitations of each paradigm. The findings indicate that Bacon’s inductivism plays a crucial role in the exploratory stage and empirical pattern identification, Mill’s causal logic functions as an inferential mechanism for explaining cause– effect relationships, and Comte’s positivism contributes to verification and scientific legitimacy. The discussion affirms that the integration of these three approaches forms a sequential methodological framework that is more adaptive to the complexity of contemporary research. The implications of this study emphasize the importance of methodological synthesis as a foundation for the development of modern epistemology and as a reference for constructing comprehensive and reflective interdisciplinary research frameworks.